The Influence of Brand Image on Purchasing Decisions for Skincare Skintific : Study on Students of the Faculty of Social Science and Political Science, Sam Ratulangi University Manado - Hungan, Fitri; Tumbel, Tinneke M; Mangindaan, Joanne V (Productivity, 2024)
The purpose of this research is to determine the influence of Brand Image on Purchasing Decisions for Skintific Skincare. This research uses basic quantitative methods. The population taken in this research were students at the Faculty of Social and Political Sciences, Sam Ratulangi University. Using the sampling technique using Purposive Sampling technique and carrying out calculations using the Slovin formula, a sample of 100 respondents was obtained. The analysis used is simple linear regression analysis, and for testing using the T Test hypothesis, Correlation Coefficient, and Determination Coefficient (R2). Keywords: Brand Image, Purchasing Decisions, Skintific.